THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON DEMINERALIZED WATER SALES VOLUME AT PT XYZ (POLITEKNIK LP3I JAKARTA, 2026)
The packaged drinking water industry in Indonesia faces increasingly intense competition, and PT XYZ, a demineralized water producer, has repeatedly failed to meet its sales volume targets during the 2024–2026 period, with shortfalls reaching 37.48%. This issue motivated a study on the influence of product quality and price on sales volume, grounded in the theoretical frameworks of product quality by Kotler and Keller (2022), pricing by Tjiptono and Chandra (2021), and sales volume by Swastha (2022). A quantitative approach was applied using total sampling involving 70 consumers as respondents. Data were collected through Likert-scale questionnaires and company documentation, then tested for validity and reliability before being analyzed using classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination via SPSS 27. The findings reveal that product quality (β = 0.631) and price (β = 0.498) each have a positive and significant effect on sales volume, both partially and simultaneously (F = 135.226; sig. 0.000), with an Adjusted R² of 79.6%. The study concludes that enhancing product quality alongside implementing competitive pricing is a key strategy for sustainably increasing sales volume of demineralized water.